2003
DOI: 10.3928/1542-8877-20030301-16
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methods for Human Retinal Oximetry

Abstract: Abstract. Attempts to noninvasively quantify the oxygen saturation of blood within the retinal vasculature date back to the 1950s. This article discusses the various approaches that have been taken to estimate the oxygen saturation in the retinal vasculature. Advantages and limitations of each are discussed. Data from human and animal subjects are also presented. [Ophthalmic Surg Lasers Imaging 2003; 34:152-164.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 41 publications
6
148
0
2
Order By: Relevance
“…To choose wavelengths for perfusion imaging of the eye a series of criteria was considered to introduce a new combination of wavelengths based on previous researches [5,12]. The criteria included safety, low absorbance, and independent scattering range.…”
Section: Beer-lambert Law For Haemoglobin Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…To choose wavelengths for perfusion imaging of the eye a series of criteria was considered to introduce a new combination of wavelengths based on previous researches [5,12]. The criteria included safety, low absorbance, and independent scattering range.…”
Section: Beer-lambert Law For Haemoglobin Saturationmentioning
confidence: 99%
“…Tiedeman [2] and Beach [3] have improved this fundus photography technique using digital images choosing as one wavelength an isobestic wavelength. A scanning oximeter, employing three wavelengths, all in the green part of spectrum, of which two are isobestic, was developed in (1988) by Delori [4] and recently by other groups who improved this method using four wavelengths [5].…”
Section: Introductionmentioning
confidence: 99%
“…OD 586 is the optical density calculated using light at 586 nm, which is insensitive to oxygen saturation. It can be shown that there exists a linear relationship [5], [6], [8] 2 SatO = ODR + a b (5) where SatO 2 is the oxygen saturation of the hemoglobin in the blood.…”
Section: Physical Basis Of Optical Oximetrymentioning
confidence: 99%
“…Noninvasive measurement of oxygenation in the human retina and optic nerve has proved technically difficult but considerable progress has been made, particularly in recent years as digital technology, in computers and cameras, has evolved. Several methods have been tried in the past (for a review of retinal oximetry methods see [6]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation